Pelestarian Budaya Masyarakat Hukum Adat Huta Sihaporas di Kabupaten Simalungun - Elma Suzana Sinaga; Reh Bungana Beru Perangin-angin (Journal on Education, 2024)
The objectives ofthis research are in the form of, (1) to find out the efforts made in preserving the Sihaporas customary law community, (2) to know the obstacles and challenges in efforts to preserve the culture of the Sihaporas customary law community, Simalungun Regency. This study uses an empirical research method supported by literature studies. The data collection process involves the use of primary and secondary data. Primary data is obtained by conducting direct observations, conducting interviews, and documenting the results, while secondary data is obtained from sources such as books, journals, and articles. The results of the study show that the efforts made in preserving the culture of the Sihaporas customary law community are; continue to carry out rituals, maintain traditional values passed down from previous generations, take care of the natural environment, and comply with customary processions and applicable regulations as well as preserve and defend ancestral heritage objects. The obstacles and challenges faced in efforts to preserve the culture of the Sihaporas customary law community are; Sihaporas has not been recognized by the government and the state until now. Public knowledge is still limited in developing networks with priority concepts, strategies, and programs at the grassroots level. as well as the lack of assistance or advocacy in helping the Sihaporas community to be recognized as an indigenous people. As well as the presence of PT. TPL seizing the Sihaporas customary forest is very disturbing, not only to the preservation of customary rituals and the continuity of agriculture, but also to ecological sustainability.